Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To determine the value of [tex]\(x\)[/tex] that would make [tex]\(\overline{KM} \parallel \overline{JN}\)[/tex], we can use the converse of the Side-Splitter Theorem. Here are the steps:
1. Identify the given ratio: By the converse of the Side-Splitter Theorem, if [tex]\( \frac{JK}{KL} = \frac{x-5}{4} \)[/tex] then [tex]\( \overline{KM} \parallel \overline{JN} \)[/tex].
2. Form the proportion: According to the theorem, we use the proportion [tex]\( \frac{x-5}{4} = \frac{3}{x} \)[/tex].
3. Cross-multiply to form an equation: [tex]\((x-5) \cdot x = 4 \cdot 3\)[/tex].
4. Distribute and set up the equation:
[tex]\[ x(x) + x(-5) = 4 \cdot 3. \][/tex]
Simplifying, we get:
[tex]\[ x^2 - 5x = 12. \][/tex]
5. Move all terms to one side of the equation to set it to zero:
[tex]\[ x^2 - 5x - 12 = 0. \][/tex]
6. Solve the quadratic equation for [tex]\(x\)[/tex]:
The solutions to the quadratic equation [tex]\(x^2 - 5x - 12 = 0\)[/tex] can be found using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -5\)[/tex], and [tex]\(c = -12\)[/tex].
By solving the quadratic equation, we get the values of [tex]\(x\)[/tex] as:
[tex]\[ x = \frac{5}{2} - \frac{\sqrt{73}}{2} \quad \text{or} \quad x = \frac{5}{2} + \frac{\sqrt{73}}{2}. \][/tex]
Therefore, the two values of [tex]\(x\)[/tex] that satisfy the condition are:
[tex]\[ x = \frac{5}{2} - \frac{\sqrt{73}}{2} \quad \text{and} \quad x = \frac{5}{2} + \frac{\sqrt{73}}{2}. \][/tex]
1. Identify the given ratio: By the converse of the Side-Splitter Theorem, if [tex]\( \frac{JK}{KL} = \frac{x-5}{4} \)[/tex] then [tex]\( \overline{KM} \parallel \overline{JN} \)[/tex].
2. Form the proportion: According to the theorem, we use the proportion [tex]\( \frac{x-5}{4} = \frac{3}{x} \)[/tex].
3. Cross-multiply to form an equation: [tex]\((x-5) \cdot x = 4 \cdot 3\)[/tex].
4. Distribute and set up the equation:
[tex]\[ x(x) + x(-5) = 4 \cdot 3. \][/tex]
Simplifying, we get:
[tex]\[ x^2 - 5x = 12. \][/tex]
5. Move all terms to one side of the equation to set it to zero:
[tex]\[ x^2 - 5x - 12 = 0. \][/tex]
6. Solve the quadratic equation for [tex]\(x\)[/tex]:
The solutions to the quadratic equation [tex]\(x^2 - 5x - 12 = 0\)[/tex] can be found using the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -5\)[/tex], and [tex]\(c = -12\)[/tex].
By solving the quadratic equation, we get the values of [tex]\(x\)[/tex] as:
[tex]\[ x = \frac{5}{2} - \frac{\sqrt{73}}{2} \quad \text{or} \quad x = \frac{5}{2} + \frac{\sqrt{73}}{2}. \][/tex]
Therefore, the two values of [tex]\(x\)[/tex] that satisfy the condition are:
[tex]\[ x = \frac{5}{2} - \frac{\sqrt{73}}{2} \quad \text{and} \quad x = \frac{5}{2} + \frac{\sqrt{73}}{2}. \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.